Problematika Kepala Madrasah dalam Melakukan Supervisi di MAN 1 Medan - Eka Lestari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims, 1) To find out the implementation of supervision of madrasa heads at MAN 1 Medan, 2) To find out the results of supervision of madrasa heads at MAN 1 Medan, and 3) To find out the problems and efforts of madrasa heads in overcoming supervision at MAN 1 Medan. This research uses qualitative research methods which are intended to determine the phenomena experienced by research subjects. With data collection techniques through observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, verification or drawing conclusions and checking the validity of the data. Using the sample, the head of the MAN 1 Medan madrasah and five different teachers to obtain information regarding the problems of the madrasah head in carrying out supervision at MAN 1 Medan. The results of this research include: 1) The implementation of supervision at MAN 1 Medan through three stages, namely, planning, implementation and follow-up evaluation which is carried out once a year, 2) The results to be achieved after supervision is carried out, namely, first for teachers, for students , and madrasah, and 3) The problem with the head of the madrasah in carrying out supervision is the limited time which makes his focus divided between his activities outside and as a supervisor at MAN 1 Medan.